Systemic lupus erythematosus with diffuse splenic calcification: A case report - Shanshan Su; Huohu Zhong (Immunity, Inflammation and Disease)
Abstract Objective Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with the main clinical characteristics of multisystem and multiorgan involvement of the whole body. It is commonly seen in skin mucosa, skeletal muscle, and the respiratory system while rarely involving the spleen. In this case, we present a young female patient with SLE with the symptom of progressing splenic calcification. Methods A 21–year–old female patient was admitted to our hospital in 2012 with complaints of “fever, abdominal pain, diarrhea, and knee pain”, and then was diagnosed with systemic lupus erythematosus combined with lupus nephritis. The first ultrasound examination was normal in 2012. However, when she returned to the hospital in 2016, she was found to have multiple calcifications in her spleen. After discharge, the patient was treated with commonly used immunosuppressive drugs and was followed up regularly for symptoms of multiple calcifications in the spleen. Results Subsequent follow–up over a long period revealed a progressive development of multiple calcifications in the spleen, with a progressive increase in the size and number of calcified foci over time. Conclusion When a patient is found to have diffuse splenic calcification on ultrasound, care should be taken to differentiate SLE with multiple splenic calcifications from sarcoidosis, tuberculosis, brucellosis, and rheumatoid arthritis in conjunction with a medical history and relevant laboratory tests.